Political parties and party system - Tunku Mohd Mokhtar, Tunku Mohar (Cengage Learning, 2008)
Political parties are part and parcel of democracies. In fact, modern democracy is unthinkable except in terms of parties. In democracies, parties offer "an excellent preliminary training for parliamentary candidature and eventual entry into parliament."l Since independence in 1957, Malaysia has experienced many general elections mostly contested by political parties and a small number of independent non-party affiliated candidates. This chapter explains the nature of political parties and party system in Malaysia. It analyses the major political parties, their objectives and bases of support. It also evaluates the nature of party system in Malaysia and weighs its strengths and weaknesses